Product Life Cycle (PLC) In Transportation Management And Speed Boat Ambulance Product Design as A Medical Solution to Realize the Sustainable Development Goals “Good Health and Prosperity” in Indonesia - Jajang Supriyatna; Apriatha Nur Fadhillah; Sarinah Sihombing; Aswanti Murgiyono (Dinasti Publisher, 2025)
This study examines the application of Product Life Cycle (PLC) in transportation management and product design of Speed Boat Ambulance as an innovative medical transportation solution in the Indonesian archipelago. By adopting a descriptive approach and literature study, this study highlights the importance of innovation in medical transportation services to improve access to health, especially in remote areas. The speed boat ambulance is considered capable of reducing response time by up to 60% compared to conventional sea transportation modes, while also addressing Indonesia's geographical challenges. The analysis also highlights the importance of ergonomic product design, the use of digital technology (such as IoT and navigation systems), and its contribution to achieving Sustainable Development Goal (SDG) 3: Good Health and Well-Being. This study recommends cross-sector collaboration and policy development that supports service sustainability to strengthen the national medical transportation system.